2009
DOI: 10.1017/s0954579409990071
|View full text |Cite
|
Sign up to set email alerts
|

Antisocial behavior from a developmental psychopathology perspective

Abstract: This paper reviews research on chronic patterns of antisocial behavior and places this research into a developmental psychopathology framework. Specifically, research suggests that there are at least three important pathways through which children and adolescents can develop severe antisocial behaviors. One group of youth shows antisocial behavior that begins in adolescence, and two groups show antisocial behavior that begins in childhood but differ on the presence or absence of callous-unemotional traits. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
421
7
17

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 489 publications
(470 citation statements)
references
References 138 publications
25
421
7
17
Order By: Relevance
“…Consistent with findings pointing to CU traits as a high-risk indicator in children with disruptive behavior (DB) disorders, there appear to be distinct developmental pathways for CU traits compared to related DB [12,13]. Children with CU traits can be distinguished from children with DB alone on the basis of genetic risk, cognitive and affective characteristics, environmental influences, biological factors, and personality traits [3].…”
Section: Cu Traits CD and Oddmentioning
confidence: 74%
“…Consistent with findings pointing to CU traits as a high-risk indicator in children with disruptive behavior (DB) disorders, there appear to be distinct developmental pathways for CU traits compared to related DB [12,13]. Children with CU traits can be distinguished from children with DB alone on the basis of genetic risk, cognitive and affective characteristics, environmental influences, biological factors, and personality traits [3].…”
Section: Cu Traits CD and Oddmentioning
confidence: 74%
“…Anomalies in these processes have been suggested in relation to the callous and unemotional features of psychopathy [Bird and Viding, 2014; Blair, 2013a; Frick and Viding, 2009], and tentatively ascribed to perturbations within the frontolimbic system discussed here [Aghajani et al, 2016; Anderson and Kiehl, 2012; Blair, 2013a, 2013b; Deeley et al, 2006; Decety et al, 2013b; Michalska et al, 2015; Moul et al, 2012]. Given the alleged interface function the CMA serves between neocortical and visceromotor structures [Bienkowski and Rinaman, 2013; Keifer et al, 2015; Pessoa, 2011], abnormalities in its neural activity and large‐scale connectivity might be particularly detrimental to this frontolimbic system, and contribute plausibly to affective traits of psychopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The developmental trajectory of psychopathy seemingly begins early in life and includes the presence of nascent psychopathic traits in conduct‐disordered juveniles [Anderson and Kiehl, 2014; Colins et al, 2014; Frick and Viding, 2009; Lynam et al, 2007]. These youngsters with psychopathic tendencies showcase a disproportionate amount of violent and antisocial acts, respond less favorably to treatment, and as such place a substantial economic and emotional burden on society [Anderson and Kiehl, 2014; Corrado et al, 2015; Frick and Viding, 2009; Salekin et al, 2010]. Yet, despite these pressing concerns the pathophysiology of psychopathic traits in these youths remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The APSD and the CU subscale in particular have been extensively validated in developmental and clinical research (P. J. Frick & Viding, 2009;Sylvers et al, 2011;van Zwieten et al, 2013), and have been shown to predict subsequent outcomes, e.g., (Wymbs et al, 2012), including the prediction to adult arrests, e.g., .…”
Section: Methodsmentioning
confidence: 99%